THE USE OF LOCAL WISDOM FROM NIAS TRADITIONAL HOUSES AS A LEARNING MEDIUM FOR CREATIVE ECONOMY AMONG STUDENTS AT SMA NEGERI 1 TELUK DALAM - Darmawan Harefa (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2025)
This study aims to examine the utilization of the local wisdom embodied in the Nias Traditional House as a learning medium for creative economy among students at SMA Negeri 1 Teluk Dalam. Motivated by the need to integrate cultural values into the learning process to enhance students’ understanding and motivation, this research employs a descriptive qualitative approach with data collected through observation, interviews, and document studies. The findings reveal that using the Nias Traditional House as a learning medium significantly increases student engagement, strengthens their understanding of creative economy concepts, and fosters an entrepreneurial spirit rooted in local cultural values. Furthermore, integrating local wisdom into the learning process supports cultural preservation and encourages students’ creativity in developing innovative business ideas. The results also highlight the crucial role of teachers and traditional leaders in facilitating participatory and contextual learning. This study recommends the development of curricula and learning media that are more adaptive to local wisdom to support sustainable and regionally relevant education.